Scheduling of Multistage Multiproduct Batch Plants Operating in a Campaign-Mode - Fumero, Yanina (2012)
In this work, mixed integer linear programming models for scheduling multistage multiproduct batch plants operating under campaign mode are proposed. It is assumed that each plant stage includes identical parallel units operating out of phase. Given the plant topology and the number of batches of each product to be processed in the campaign, the objective is assigning batches to units in each stage in order to minimize the cycle time of the campaign. An asynchronous slot-based continuous-time representation for modeling the assignment of batches to units is used. These formulations require postulating a priori a suitable number of production slots for each unit that integrates the plant, which severely affects the model computational performance. Then, to reduce the computational effort, a solution strategy is proposed where a simplified model, which includes preordering constraints, is first solved. Finally, a detailed scheduling model is posed where the optimal cycle time of simplified model is used as bound for the cycle time and a novel expression for the number of proposed slots for each unit is considered. The strategy is highlighted through examples that show how the computational burden is reduced.